RANCANG BANGUN SISTEM KONTROL DAN MONITOR PRODUKSI GARAM MENGGUNAKAN INTERNET OF THINGS - Prihatmoko, Dias; Mustofa, Arif; Faidlon, Ahmad; Arifin, Zaenal (Universitas Islam Nahdlatul Ulama Jepara, 2024)
DESIGNING A SALT PRODUCTION CONTROL AND MONITOR SYSTEM USING INTERNET OF THINGSSalt is a part of the national strategic commodity whose position is no less important compared to other basic needs. Currently, the national salt demand balance is 4.5 million tonnes. Salt farmers, so far, still use conventional and traditional methods, the salting process using a measuring instrument in the form of a salt baume hydrometer with a range of 0 – 35 manually. This results in farmers having to measure at all times at the salt pond location. Therefore, it is necessary to have a tool that can control and monitor salt content values. By using this tool, the process of monitoring salt content values can run quickly, effectively and efficiently. This research uses a WiFi-based ESP8266 microcontroller, salt content sensors and temperature and humidity sensors. Salt content sensors are placed in old water and salt tables, while temperature and humidity sensors are placed in salt storage locations. The sensor reads data on salt levels, temperature and humidity which is then sent to the microcontroller so that the information can then be monitored at any time by salt farmers. The results of this research, the control and monitoring system for salt production using the internet of things has been successfully tested and obtained good results, it can monitor and control salt production, the main ones are salt content, temperature and humidity, the average error percentage is 2, 8% when measuring the salt content of old water, and 3 percent when measuring the salt content on a salt table. Meanwhile, in the control system, the fan is turned on according to the setting, namely above 30 degrees Celsius, the fan will turn on, then the conditions in the salt storage room can run at optimal temperature so as to minimize the decrease in salt levels during storage.Garam merupakan salah satu bagian dari komoditas strategis nasional yang posisinya tidak kalah penting jika dibanding dengan kebutuhan pokok lainnya, saat ini neraca kebutuhan garam nasional sebesar 4,5 juta Ton. Para petani garam, selama ini masih menggunakan cara konvensional dan tradisional, proses penggaraman menggunakan alat ukur berupa hydrometer baume garam dengan range 0 – 35 secara manual. Hal ini mengakibatkan para petani harus mengukur setiap saat ke lokasi tambak garam. Oleh karena itu perlu adanya alat yang dapat mengontrol dan memonitor nilai kadar garam, Dengan pengggunaan alat tersebut maka proses pemantauan nilai kadar garam dapat berjalan secara cepat, efektif, dan efisien. Penelitian ini menggunakan mikrokontroller ESP8266 berbasis wifi, sensor kadar garam serta sensor suhu dan kelembaban. Sensor kadar garam ditempatkan di air tua dan meja penggaraman, sedangkan sensor suhu dan kelembaban di tempatkan di lokasi penyimpanan garam. Sensor membaca data kadar garam, suhu dan kelembaban kemudian dikirim ke mikrokontroller untuk selanjutnya informasi dapat dipantau setiap saat oleh petani garam. Hasil penelitian ini, sistem control dan monitoring produksi garam dengan menggunakan internet of things ini telah berhasil di uji coba dan mendapatkan hasil yang baik, dapat memonitor dan control produksi garam utamanya adalah kadar garam, suhu dan kelembaban, rata-rata prosentase error sebesar 2,8 % saat mengukur kadar garam air tua, dan sebesar 3 persen saat mengukur kadar garam di meja penggaraman. Sedangkan sistem control nya, kipas menyala sesuai dengan pengaturan yaitu diatas 30 derajat celcius maka kipas akan menyala, selanjutnya kondisi ruang penyimpanan garam dapat berjalan pada suhu optimal sehingga dapat meminimalisir penurunan kadar garam selama penyimpanan.